Using Electronic Device for Muscular Strenght Determination - Benedek, F.; Leuciuc, F. V. (Elektronika ir Elektrotechnika, 2010)
Introducing the latest technologies and equipments în sport activities has considerably increased the quality of these activities. In our research we used 4 tests to determine the muscular strength: Bench press, Plyometric jump, Counter movement jump and Squat jump. The obtained achievements between the 2 testings are significantly higher for group 2 (3.67%), comparing to group 1 (1.46%), because longer duration for practising motric activities has increased the performance for those tests. The device used in the research (Myotest) helps to get some valuable data regarding ways of manifesting the motric aptitude – force, present in most of the motric activities. The obtained results allow practicing optimal physical exercises for recreation as well as performance at the highest level.